Extraction of chromium (VI) in water samples by dispersive liquid–liquid microextraction based on deep eutectic solvent and determination by UV–Vis spectrophotometry. Issue 10 (8th August 2020) - Pourmohammad, Mahsa; Faraji, Mohammad; Jafarinejad, Shahryar
ABSTRACT: In this research, a simple, green, sensitive and fast method was developed based on deep eutectic solvent dispersive liquid-liquid microextraction (DES-DLLME) to extract trace amount of Cr(VI) from water samples followed by spectrophotometry determination via microcell. The new DES solvent was prepared by mixing phenol as hydrogen bonding donor and benzyltriethyl ammonium chloride as hydrogen acceptor at 50ºC for 5 min. The impact of various factors in complexation and microextraction steps were evaluated and optimised in detail. Under optimum conditions, calibration graph was linear in the range of 5.0–200 µg L −1 . The limit of detection (LOD), the limit of quantification (LOQ), enrichment factor and relative standard deviation were obtained 1.5 µg L −1, 5.0 µg L −1, 73 and 5.01%, respectively. Finally, the proposed method was successfully employed for determination of Cr(VI) in water and wastewater samples and satisfactory recoveries (≥90%) was obtained.